"Eskimo chicks and word warriors": the creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)

Alanis Obomsawin: The Vision of a Native Filmmaker - Lewis, Randolph (University of Nebraska Press, 2006)
In more than twenty powerful films, Abenaki filmmaker Alanis Obomsawin has waged a brilliant battle against the ignorance and stereotypes that Native Americans have long endured in cinema and television. In this book, the first devoted to any Native filmmaker, Obomsawin receives her due as the central figure in the development of indigenous media in North America.

Oralité et culture vocale inuit - Le Goff, Philippe (Revue DEMéter, 2003)

Native American Contemporary Music: The Women - Diamond, Beverley (The World of Music, 2002)
This article explores issues raised in interviews with traditional and contemporary Native American musicians and recording artists of the 1990s. It exemplifies how they view their roles vis à vis traditional gender structures and community obligations, how they draw upon different media to communicate their messages, and how they use their work as a form of social action. Their narratives reveal a wide variety of strategies by which they negotiate the double consciousness and multiple relationships of their lives, balancing historically rooted values and traditions with modern ones. I attempt to develop a feminist interpretation that is respectful of the cultural values these women expressed in their conversations with me.
Publisher: [Florian Noetzel GmbH Verlag, VWB - Verlag für Wissenschaft und Bildung, Schott Music GmbH & Co. KG, Bärenreiter]